Stability of Hand Body Gel Formulated with Avocado (Persea americana), Stingless Bee Honey, and Bee Pollen - Fauziyah, Nur; Kustiawan, Paula Mariana (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
The development of hand body care products in gel form, incorporating natural ingredients, remains an underexplored area, particularly concerning the combination of avocado (Persea americana) extract, Stingless bee (Trigona sp.) honey, and pollen in cosmetic formulations. Gel formulations are favored for their superior skin moisturizing properties and enhanced dermal absorption compared to lotions. This study aimed to evaluate the stability and moisturizing efficacy of novel hand body gel formulations containing varying ratios of P. americana extract combined with Trigona bee pollen and honey. Employing an experimental quantitative design, three distinct gel formulations were prepared with different concentrations of P. americana extract with Trigona bee pollen and honey. The stability of these formulations as skin moisturizers was assessed through a comprehensive evaluation encompassing organoleptic properties, homogeneity, potential for irritation, pH, spreadability, viscosity, and moisture content analysis using skin analysis instrumentation. The results indicated that the gel formulation designated F1, containing 2.5% P. americana extract and 7.5% honey combined with bee pollen, exhibited the highest skin moisture content, suggesting its potential as an effective moisturizing hand body gel.